Comparative analysis of novel grease formulations from used transformer and engine oils - Muhammad Auni, Hairunnaja; Mohd Aizudin, Abd Aziz; Mohd Azmir, Arifin; Nur Amira Fatihah, Bashari; Nedumaran, Navinash; Khairuddin, Md Isa (Malaysian Tribology Society (MYTRIBOS), 2025)
Addressing the dwindling mineral oil supply and the improper disposal of used transformer oil (UTO) and used engine oil (UEO). This study formulates greases from these used oils (UOs) to compare their performances. UTO and UEO are considered wastes and often disposed of improperly due to a lack of awareness on their environmental impacts. Hence, the study focuses on formulating greases from UTO and UEO through several processes, involving the treatment of these UOs to eliminate contaminants, addition of thickener and additives during grease formulation, and subsequent testing for consistency, oil separation, dropping point, corrosion resistance, coefficient of friction (COF) and wear scar diameter (WSD) value for the grease performance analysis. All greases exhibit NLGI values of 2-3, oil bleeding within (-15% - 15%), dropping points ranging from 180℃ to 240℃ for sodium grease and over 350℃ for fumed silica (F.S.) grease, oil separation below 4%, with slight tarnishing in corrosion tests. The top-performing grease, FG84.7G, stands out with the highest dropping point with lowest COF and WSD value, making it the most optimal choice. The study concludes that UTO and UEO are effective base oils for grease due to their satisfactory performance.